Programmed instructional materials on relative pronouns for first year - Cabato, Carmen (Magdalena) (Quezon City [s.n.], 1974)
This is a design of a programmed text to be used for teaching English relative pronouns efficiently and effectively to Tagalog speaking first year students. These programmed lessons are constructed based on the problems found in Tagalog speakers in learning English relative pronouns.
Thesis (M.A.T.)--University of the Philippines.
Keywords: English language -- Programmed instruction; English language -- Study & teaching -- Filipino students